Groundwater quality and its hydrochemical characteristics in a shallow weathered rock aquifer of southern India - Rajesh, R.; Brindha, Karthikeyan; Elango, L. (Springer, 2015)
Suitability of groundwater for domestic and irrigation purposes as well as its hydrochemical characteristics was estimated in a part of Nalgonda district, Telangana state in southern India. Water samples were collected from 45 wells once every 2 months from March 2008 to January 2010. EC and pH were measured in situ while concentrations of calcium, magnesium, sodium, potassium, sulphate and chloride in groundwater were analysed using ion chromatograph. Carbonate and bicarbonate concentration were determined by acid base titration. General order of dominance of cations in the groundwater of this study area is Na?[Ca2?[Mg2?[ K? while that for anions is HCO3 -[Cl-[SO4-2. Ca–HCO3, Na–Cl, mixed Ca–Na–HCO3 and mixed Ca–Mg–Cl types of groundwater were dominant in this area. Groundwater is generally fresh with medium to high salinity and low alkalinity. Chloride and bicarbonate concentrations were present within the permissible limits for drinking whereas, some samples exceed the permissible limits of the Bureau of Indian Standards for pH, TDS, TH,sodium, calcium, magnesium and sulphate. Potassium exceeded the maximum permissible limits for drinking proposed by World Health Organisation. Sodium adsorption ratio, sodium percentage, residual sodium carbonate and permeability index indicates that the groundwater quality was suitable for irrigation in most parts of the study area.